Comparison Formwork Wood Sloof to Batako Viewed from the Aspect of Time and Cost - Michael Tedja; Hendra Halim; Kezia Divaninta; Valentina Hidayat (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Concrete-Mold is one of the most important elements of a building’s structural system. Like other structural systems, the concrete mold placed right after the main wiring structure placed. The function of the concrete mold is to specify the size of the concrete structure itself. The needs of an efficient construction timeand cost are some reasons of the decent and fast development of home-design structure. Sloof’s concrete-mold for two-floor houses can be done with two different materials, i.e. wooden plywood material and bricks. The difference usage of these two materials is the background of this research. The purpose of research is to find out the best way in time and cost efficiency of these two materials. This research carried out using the method of library studies, survey, and comparative study. The result of this research showed that the cost of the brick making the job of sloof concrete mold cheaper and faster. Thus, sloof concrete mold making is one of the project solutions that are more efficient in terms of time and cost.